Factors Associated with Sadari Behavior in Undana FKM Female Students Class of 2023 - Marcianus Ratu; Marni Marni; Petrus Romeo; Ribka Limbu (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Breast cancer is an abnormal cell growth in the breast that forms a tumor. Starting from the milk ducts or lobules, cancer cells can spread to surrounding tissues of the body and form a lump or thickening. If left untreated, cancer can metastasize and become life-threatening. Breast self-examination (SADARI) is an effective method of early detection, but the rate of implementation is still low among women. Objective: This study aims to determine the relationship between knowledge, attitudes and peer support with SADARI behavior in public health study program students of FKM UNDANA class of 2023. Method: The research method used was quantitative with a cross-sectional approach. The sample consisted of 50 female students of FKM UNDANA class of 2023 who were determined by simple random sampling technique. Data were collected using a questionnaire in the form of a google form and analyzed using the chi-square test. Result: The results showed a significant relationship between knowledge (p=0.001), attitude (p=0.001), and peer support (p=0.000) with SADARI behavior. Most of the respondents had good knowledge (48%), positive attitude (70%), and good peer support (50%). Conclusion: FKM Undana students need to increase their knowledge and positive attitude towards SADARI, making it a monthly routine. They should support each other and create an environment that encourages the practice of early detection of breast cancer.